Temporal changes in pulmonary gas exchange efficiency when breath‐hold diving below residual volume. Issue 4 (12th March 2021) - Patrician, Alexander; Spajić, Boris; Gasho, Christopher; Caldwell, Hannah G.; Dawkins, Tony; Stembridge, Michael; Lovering, Andrew T.; Coombs, Geoff B.; Howe, Connor A.; Barak, Otto; Drviš, Ivan; Dujić, Željko; et al.
Abstract : New Findings: What is the central question of this study? How does deep breath‐hold diving impact cardiopulmonary function, both acutely and over the subsequent 2.5 hours post‐dive? What is the main finding and its importance? Breath‐hold diving, to depths below residual volume, is associated with acute impairments in pulmonary gas exchange, which typically resolve within 2.5 hours. These data provide new insight into the behaviour of the lungs and pulmonary vasculature following deep diving. Abstract: Breath‐hold diving involves highly integrative and extreme physiological responses to both exercise and asphyxia during progressive elevations in hydrostatic pressure. Over two diving training camps (Study 1 and 2), 25 breath‐hold divers (recreational to world‐champion) performed 66 dives to 57 ± 20 m (range: 18–117 m). Using the deepest dive from each diver, temporal changes in cardiopulmonary function were assessed using non‐invasive pulmonary gas exchange (indexed via the O2 deficit), ultrasound B‐line scores, lung compliance and pulmonary haemodynamics at baseline and following the dive. Hydrostatically induced lung compression was quantified in Study 2, using spirometry and lung volume measurement, enabling each dive to be categorized by its residual volume (RV)‐equivalent depth. From both studies, pulmonary gas exchange inefficiency – defined as an increase in O2 deficit – was related to the depth of the dive ( r 2 = 0.345; P < 0.001), with dives associated with lung squeeze symptoms exhibiting the greatest deficits. In Study 1, although B‐lines doubled from baseline ( P = 0.027), cardiac output and pulmonary artery systolic pressure were unchanged post‐dive. In Study 2, dives with lung compression to ≤RV had higher O2 deficits at 9 min, compared to dives that did not exceed RV (24 ± 25 vs. 5 ± 8 mmHg; P = 0.021). The physiological significance of a small increase in estimated lung compliance post‐dive (via decreased and increased/unaltered airway resistance and reactance, respectively) remains equivocal. Following deep dives, the current study highlights an integrated link between hydrostatically induced lung compression and transient impairments in pulmonary gas exchange efficiency. Abstract :